Memory and standing balance after multisensory stimulation in a Snoezelen room in people with moderate learning disabilities. - Toro, Brigitte (British Journal of Learning Disabilities, 2019)
Accessible Summary: Multisensory stimulation improves attention, which can also improve memory and standing balance of people with learning disabilities, even at a high age.Improved standing balance and body awareness may help reduce falls in people with moderate learning disabilities.Therapeutic treatments could be more effective if preceded by multisensory stimulation. Background: The Snoezelen room provides a multisensory environment for people with learning disabilities. Method: Thirty‐five residents were recruited from a convenience sample of people living in a residential centre. A repeated‐measures, within‐subject design was used to evaluate the participants during three conditions: a) Snoezelen room, b) control period and c) watching television. The outcome measures were digit span memory tests and Romberg balance tests. One‐way repeated‐measures ANOVAs and paired‐samples t tests were performed on the data. Results: ANOVA results show that there was a significant effect over time in the amount of digits remembered and in balancing ability between the three conditions (p < .0005). T tests confirmed that the Snoezelen condition was responsible for the significant improvements in memory and balancing ability. Conclusion: Participants performed significantly better with memory tasks and balancing skills after having attended multisensory stimulation in a Snoezelen room. This may be due to improved mindfulness, which is correlated with improvements of concentration, learning ability and motor skills caused by neurophysiologic changes of the brain.